2020
DOI: 10.1177/2327857920091024
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of FDA Adverse Event Reporting Data for Trends in Medical Device Use Error

Abstract: Humans can contribute to error at all stages of the medical device product life-cycle. Use error associated with medical devices can result in catastrophic consequences for end users and inefficient use of healthcare system resources. Industry-wide statistics about medical device use error has the potential to aid in identifying opportunities for human factors intervention, however publicly available statistics are sparse. The Food and Drug Administration (FDA) requires medical device manufactures, importers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It was observed in this study that an increase in alarm fatigue in the participants increased their tendency to make errors in patient follow‐up and material safety, which are among the dimensions of METSN (Table 3). Knisely et al 37 reported that checking the expiration dates of the consumables used checking the devices before use would be effective in preventing errors related to the use of materials and devices. Kahraman 21 stated that the use of devices without checking their details by nurses causes medical errors because it delays the treatment process.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed in this study that an increase in alarm fatigue in the participants increased their tendency to make errors in patient follow‐up and material safety, which are among the dimensions of METSN (Table 3). Knisely et al 37 reported that checking the expiration dates of the consumables used checking the devices before use would be effective in preventing errors related to the use of materials and devices. Kahraman 21 stated that the use of devices without checking their details by nurses causes medical errors because it delays the treatment process.…”
Section: Discussionmentioning
confidence: 99%
“… 1 – 3 Currently, a great deal of research into digital health harms focuses on the role of manufacturers and regulatory agencies in improving device oversight, however these interventions can be slow to implement, and need to be paired with changes on the floor of clinical practice. 21 28 Given that research has demonstrated that 96.6% of reports on regulatory platforms such as FDA MAUDE database are made by manufacturers (as opposed to treating clinicians), it is perhaps unsurprising that a clinical perspective has been lacking when designing a response to these events. 23 In our research we utilise simulation methods in order to centre the clinician–patient interaction during digital events, and examine the gaps in knowledge, training and resources that impede effective medical care during these scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a great deal of research into digital health harms focuses on the role of manufacturers and regulatory agencies in improving device oversight, however these interventions can be slow to implement, and need to be paired with changes on the floor of clinical practice (21)(22)(23)(24)(25)(26)(27)(28). Given that research has demonstrated that 96.6% reports on regulatory platforms such as FDA MAUDE database are made by manufacturers (as opposed to treating clinicians), it is perhaps unsurprising that a clinical perspective has been lacking when designing a response to these events (23).…”
Section: Introductionmentioning
confidence: 99%